2017
DOI: 10.1111/ggi.12958
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caregiving relationship and formal long‐term care service use on caregiver well‐being

Abstract: Developing a better understanding of the associations between well-being and formal LTC service use for different types of patient-caregiver relationships is critical for policy makers and healthcare providers who aim to create holistic systems of care. Geriatr Gerontol Int 2017; 17: 1714-1721.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…more depressive symptoms and experience of stress than noncaregivers) (Pinquart & Sorensen, ; Smith, Williamson, Miller, & Schulz, ). In a study done in Singapore, it was found that spousal and adult children caregivers reported poorer well‐being compared with nonimmediate family members who provided care (Eom, Penkunas, & Chan, ). Nonetheless, not all caregiving experiences are negative; many family caregivers also report positive experiences from caregiving such a sense of personal growth, increased meaning and purpose in life (Peacock et al, ).…”
Section: Background and Research Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…more depressive symptoms and experience of stress than noncaregivers) (Pinquart & Sorensen, ; Smith, Williamson, Miller, & Schulz, ). In a study done in Singapore, it was found that spousal and adult children caregivers reported poorer well‐being compared with nonimmediate family members who provided care (Eom, Penkunas, & Chan, ). Nonetheless, not all caregiving experiences are negative; many family caregivers also report positive experiences from caregiving such a sense of personal growth, increased meaning and purpose in life (Peacock et al, ).…”
Section: Background and Research Aimsmentioning
confidence: 99%
“…more depressive symptoms and experience of stress than noncaregivers) (Pinquart & Sorensen, 2011;Smith, Williamson, Miller, & Schulz, 2011). In a study done in Singapore, it was found that spousal and adult children caregivers reported poorer well-being compared with nonimmediate family members who provided care (Eom, Penkunas, & Chan, 2017).…”
Section: Backg Round and Re S E Arch Aimsmentioning
confidence: 99%
“…A similar fluctuating trend is also observed in the OECD average (OECD 2011, 2013, 2015). Eom, Penkunas and Chan (2017) found that immediate family care-givers experience lower wellbeing and higher subjective burden than non-immediate family care-givers. Also societal changes, for instance the increase in retirement age, the individualisation of lifestyles and weakening norms of family obligations may reduce the family member's possibilities to engage in an informal care relationship (Anttonen and Häikiö 2011; Fingerman et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is the family that bears the largest burden of elderly care provision in Singapore. Scholars and advocacy groups have documented the immense pressures that such a responsibility has placed on Singaporean caregivers, particularly in the context of shrinking families and higher costs of living (Eom et al 2017;Tan et al 2012). This has created a phenomenon that Ochiai (2011) calls 'liberal familialism', in which a family turns to the market to find a solution to its filial care responsibilities.…”
Section: Cracks In the Elderly Care Diamond: The Case Of Singaporementioning
confidence: 99%